A novel SINE family occurs frequently in both genomic DNA and transcribed sequences in ixodid ticks of the arthropod sub-phylum Chelicerata - Sunter, J.D.; Patel, S.P.; Skilton, Robert A.; Knowles, Donald P.; Scoles, Glen A.; Nene, Vishvanath M.; Villiers, Etienne P. de; Bishop, Richard P. (Elsevier, 2008)
Reassociation kinetics and flow cytometry data indicate that ixodid tick genomes are large, relative to most arthropods, containing ≥ 109 base pairs. The molecular basis for this is unknown. We have identified a novel small interspersed element with features of a tRNA-derived SINE, designated Ruka, in genomic sequences of Rhipicephalus appendiculatus and Boophilus (Rhipicephalus) microplus ticks. The SINE was also identified in expressed sequence tag (EST) databases derived from several tissues in four species of ixodid ticks, namely R. appendiculatus, B. (R.) microplus, Amblyomma variegatum and also the more distantly related Ixodes scapularis. Secondary structure predictions indicated that Ruka could adopt a tRNA structure that was, atypically, most similar to a serine tRNA. By extrapolation the frequency of occurrence in the randomly selected BAC clone sequences is consistent with approximately 65,000 copies of Ruka in the R. appendiculatus genome. Real time PCR analyses on genomic DNA indicate copy numbers for specific Ruka subsets between 5800 and 38,000. Several putative conserved Ruka insertion sites were identified in EST sequences of three ixodid tick species based on the flanking sequences associated with the SINEs, indicating that some Ruka transpositions probably occurred prior to speciation within the metastriate division of the Ixodidae. The data strongly suggest that Class I transposable elements form a significant component of tick genomes and may partially account for the large genome sizes observed.